ASSISTANT TEACHER’S ROLE IN AUTONOMOUS LEARNER METHOD - Xabibullayev , Xakimxo‘ja Xamidulla o‘g‘li (Educational Research in Universal Sciences, 2023)
Education is becoming more challenging day by day requiring being competitive and reaching the highest potential of each learner by giving attention to learner autonomy. Although former researchers gave the outline of the qualities of autonomous learners and the responsibilities of assistant teachers well, checking the correlation between easing the process of learning to achieve success of foreign language learners leads to this research. Our finding proves that an assistant teacher’s role has more effect on study skills and achieving better results.